Economic and socio-cultural impacts of Mainland Chinese tourists on Hong Kong residents - Manisa Piuchan (2018)
© 2017 Kasetsart University The aim of this study was to investigate the economic and socio-cultural impacts from the burgeoning mainland Chinese tourists on Hong Kong residents. Ten individual, semi-structured interviews were conducted to collect Hong Kong residents' views. Content analysis was employed to analyze the data. The results showed that the socio-cultural aspects were reported negatively with regard to culture, shopping and dining, and transportation but conversely, it had a positive impact on education and infrastructure. The economic aspect showed that residents accepted and appreciated the economic benefits brought by the inflow of mainland Chinese tourists. The Hong Kong government should consider these impacts, and then provide better solutions for residents' lives and plans to cope with the upcoming scenario which might arise regarding Hong Kong's economic boom and more tourists traveling to Hong Kong. Recommendations are also suggested in this study for further development.